Áine Mangaoang, John O’Flynn and Lonán Ó Briain (eds), Made in Ireland: Studies in Popular Music (2021) - Williams, Sean (Journal of the Society for Musicology in Ireland, 2022)
A review of Áine Mangaoang, John O’Flynn and Lonán Ó Briain (eds), Made in Ireland: Studies in Popular Music (New York: Routledge, 2021). ISBN 9781138336032